Effect of chemical potential on the structural modification of titanate-based photocatalysts: Fast dye degradation efficiency and adsorption power - Pereira, Chrystopher A.M. [UNESP]; Amoresi, Rafael A.C. [UNESP]; Teixeira, Guilhermina F.; Oliveira, Regiane C.; Coleto Jr, Ubirajara; da Luz, Angélica R. [UNESP]; de Almeida, Priscila B.; Simões, Alexandre Z. [UNESP]; Monteiro Filho, Elias S. [UNESP]; Longo, Elson; Perazolli, Leinig A. [UNESP] (Elsevier, 2023)
In this work, the impact of the chemical potential of sodium hydroxide concentration was evaluated in the synthesis of titanate-based photocatalysts prepared by the microwave-assisted hydrothermal method. The materials were characterized by techniques that made it possible to unveil their structural, morphological, and electronic properties, corroborating the formation of a heterojunction of sodium titanate (Na2Ti6O13) and hydrated hydrogen titanate (H2Ti3O7·H2O). The results demonstrated that the increased chemical potential of NaOH caused an ionic exchange between Na+ and H+ ions, making the H2Ti3O7·H2O phase more stable. The oriented attachment (OA) growth mechanism was predominant, resulting in nanoparticles with nanosheet-like morphology. The photocatalytic efficiency of the materials was tested for the discoloration of Rhodamine B (RhB) and Methylene Blue (MB) dyes. The photocatalyst with the best efficiency showed a half-life time for RhB discoloration of only 5 min and a high capacity of adsorption in the MB medium (∼90% in 10 min). The details of the nanoparticle growth mechanism, the charge transport in the heterojunction, and the stability and reusability of the materials were clarified.
Keywords: Chemical potential; Dye discoloration; Microwave-assisted hydrothermal method; Photocatalysts; Titanate-based nanosheets